ANALISIS BEBERAPA FAKTOR DETERMINAN YANG MEMPENGARUHI KINERJA KEUANGAN - Dicky Arisudhana; Ravindra Safitra Hidayat; Yugi Setyarko; Agus Sriyanto (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
This research aims to determine and test the influence of several financial ratios, namely liquidity, leverage, sales growth and debt maturity on financial performance. This type of research is quantitative research that uses secondary data sourced from the website www.idx.co.id. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange with an observation period of 2018-2022. The sampling technique used a purposive sampling method and a total sample of 44 companies was obtained. The analysis method in this research uses a multiple linear regression test with the research results showing that the current ratio and sales growth have a significant effect in a positive direction on financial performance, while leverage and debt maturity have a significant effect in a negative direction on financial performance.